Analisis Faktor-Faktor yang Mempengaruhi Kinerja Pengadaan, Studi Kasus pada Organisasi Kemanusiaan Palang Merah Indonesia - Rizki Sulaeman; Wahyuningsih Santosa; Ratna Darasih; Dorina Widowati (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study aims to analyze the factors influencing procurement performance in humanitarian organizations, specifically the Indonesian Red Cross (PMI), by examining the effect of information integration on procurement performance and testing the mediating roles of internal procurement control and procurement standardization. Research Design and Methodology: This study employs a quantitative research design using a cross-sectional approach to analyze factors affecting procurement performance in humanitarian organizations. Data were collected through an online questionnaire distributed to 175 respondents from the Indonesian Red Cross (PMI) in Jakarta. The variables include information integration, internal procurement control, procurement standardization, and procurement performance. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to test both direct and mediating relationships among the constructs. Findings and Discussion: The results reveal that information integration has a significant positive effect on procurement performance, internal procurement control, and procurement standardization. Procurement standardization also significantly improves procurement performance, while internal control shows no direct significant impact. Moreover, internal control and standardization jointly mediate the relationship between information integration and procurement performance. These findings highlight the crucial role of information sharing, control mechanisms, and standard procedures in enhancing efficiency, transparency, and effectiveness within humanitarian procurement systems. Implications: The findings suggest that humanitarian organizations should strengthen information integration and establish robust internal control and standardized procurement procedures to improve efficiency, transparency, and overall procurement performance.